1998
DOI: 10.1037/0022-3514.74.2.420
|View full text |Cite
|
Sign up to set email alerts
|

Resilience–recovery factors in post-traumatic stress disorder among female and male Vietnam veterans: Hardiness, postwar social support, and additional stressful life events.

Abstract: Structural equation modeling procedures were used to examine relationships among several war zone stressor dimensions, resilience-recovery factors, and post-traumatic stress disorder symptoms in a national sample of 1,632 Vietnam veterans (26% women and 74% men). A 9-factor measurement model was specified on a mixedgender subsample of the data and then replicated on separate subsamples of female and male veterans. For both genders, the structural models supported strong mediation effects for the intrapersonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
351
4
13

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 532 publications
(398 citation statements)
references
References 119 publications
30
351
4
13
Order By: Relevance
“…Results of univariate analyses were consistent with those from other studies showing that the development of PTSD is associated with numerous premilitary, military, and postmilitary factors (e.g., Green et al, 1990;King et al, 1998). The maintenance of PTSD was associated with ethnicity, lower premilitary education, more severe punishment, a higher amount of warzone exposure, peritraumatic dissociation, lower social support at homecoming, lower current social support, and a higher number of recent life events.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Results of univariate analyses were consistent with those from other studies showing that the development of PTSD is associated with numerous premilitary, military, and postmilitary factors (e.g., Green et al, 1990;King et al, 1998). The maintenance of PTSD was associated with ethnicity, lower premilitary education, more severe punishment, a higher amount of warzone exposure, peritraumatic dissociation, lower social support at homecoming, lower current social support, and a higher number of recent life events.…”
Section: Discussionsupporting
confidence: 86%
“…We followed the selection and creation of variables used in a series of studies that identified risk factors for current chronic PTSD in the NVVRS lay-interview sample (King et al, 1996(King et al, , 1998King, King, Foy, Keane, & Fairbank, 1999). Onset of depression also was examined given findings on the role of depression in the development and maintenance of PTSD (e.g., Freedman, Brandes, Peri, & Shalev, 1999).…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…However, numerous factor analytic studies conducted across different trauma populations (e.g., male combat veterans, female sexual assault survivors, etc.) and assessment instruments [e.g., Clinically Administered PTSD Scale (Blake et al, 1995), Posttraumatic Stress Disorder Checklist (Weathers, Litz, Huska, & Keane, 1994), Mississippi PTSD Scale (Keane, Caddell, & Taylor, 1988)] have found differing solutions ranging from two (Buckley, Blanchard, & Hickling, 1998;Foa, Riggs, & Gershuny, 1995;Taylor, Kuch, Koch, Crockett, & Passey, 1998), three (Cordova, Studts, Hann, Jacobsen, & Andrykowski, 2000;Cox, Clara, & Enns, 2002;Thatcher & Krikorian, 2005), and four factors (Andrews, Joseph, Shevlin, & Troop, 2006;Asmundson et al, 2000;King, King, Fairbank, Keane, & Adams, 1998;McWilliams, Cox, & Asmundson, 2005;Palmieri & Fitzgerald, 2005;Simms, Watson, & Doebbeling, 2002). We would expect that if the DSM-IV organization of PTSD symptoms were robust, the organization of three domains would be supported across populations and different operationalizations of symptom indices.…”
Section: Factor Structure Of Ptsdmentioning
confidence: 99%